Spread Love Not Hate : Edukasi Pencegahan Bullying di Lingkungan Sekolah Dasar - Alvianti Khoirunnisa2; Elin Herlina; Indri Eliyani; candra destiyanti, ika (Jurnal Pengabdian Kepada Masyarakat, 2024)
This research aims to improve the knowledge of bullying among sixth- grade students at SDN 1 Salareuma through the implementation of educational video screening methods. The subjects of this research are the number of sixth-grade students at SDN 1 Salareuma. While the object of this research is the variable of using educational video screening methods aimed at increasing students' knowledge of bullying in the sixth grade. This research uses Classroom Action Research (CAR). The research will be conducted in 1 pre-action and 1 cycle, which includes Planning, Acting, Observing, and Reflecting. The data collection techniques are observation, pre-test, post-test, and documentation. This data will be obtained from primary and secondary data. The data is collected to find out how far the implementation of bullying education in improving students' knowledge about bullying prevention efforts. Through lectures and educational video screenings, this research involved 15 sixth-grade students at SDN 1 Salareuma. The results of the study show that this education program was successful because there was a decrease from 80% to 26.7%, thus increasing students' awareness of the impact of bullying, as well as knowledge of bullying. The results show that bullying is a complex problem that requires a comprehensive approach. This research highlights the importance of education as one of the efforts to prevent bullying in elementary schools. The "Spread Love Not Hate" education program developed in this research by student volunteers aims to equip students with the knowledge, skills, and values needed to prevent and address bullying. The results of this study show that this education program has the potential to create a more positive and inclusive school environment. These findings can serve as a basis for the development of more effective bullying prevention policies and programs at the school, regional, and national levels.